A Large-Scale Genome-Wide Association Analyses of Ethiopian Sorghum Landrace Collection Reveal Loci Associated With Important Traits - Girma, Gezahegn; Nida, Habte; Seyoum, Amare; Mekonen, Moges; Nega, Amare; Lule, Dagnachew; Dessalegn, Kebede; Bekele, Alemnesh; Gebreyohannes, Adane; Adeyanju, Adedayo; Tirfessa, Alemu; Ayana, Getachew; et al. (Frontiers in Plant Science, 2019)
The eastern Africa region, Ethiopia and its surroundings, is considered as the center of origin and diversity for sorghum, and has contributed to global sorghum genetic improvement. The germplasm from this region harbors enormous genetic variation for various traits but little is known regarding the genetic architecture of most traits. Here, 1425 Ethiopian landrace accessions were phenotyped under field conditions for presence or absence of awns, panicle compactness and shape, panicle exsertion, pericarp color, glume cover, plant height and smut resistance under diverse environmental conditions in Ethiopia. In addition, F1 hybrids obtained from a subset of 1341 accessions crossed to an A1 cytoplasmic male sterile line, ATx623, were scored for fertility/sterility reactions. Subsequently, genotyping-by-sequencing generated a total of 879,407 SNPs from which 72,190 robust SNP markers were selected after stringent quality control. Pairwise distance-based hierarchical clustering identified 11 distinct groups. Of the genotypes assigned to either one of the 11 sub-populations, 65% had high ancestry membership coefficient with the likelihood of more than 0.60 and the remaining 35% represented highly admixed accessions. A genome-wide association study (GWAS) identified loci and SNPs associated with aforementioned traits. GWAS based on compressed mixed linear model identified SNPs with significant association (FDR ≤ 0.05) to the different traits studied. The percentage of total phenotypic variation explained with significant SNPs across traits ranged from 2 to 43%. Candidate genes showing significant association with different traits were identified. The sorghum bHLH transcription factor, ABORTED MICROSPORES was identified as a strong candidate gene conditioning male fertility. Notably, sorghum CLAVATA1 receptor like kinase, known for regulation of plant growth, and the ETHYLENE RESPONSIVE TRANSCRIPTION FACTOR gene RAP2-7, known to suppress transition to flowering, were significantly associated with plant height. In addition, the YELLOW SEED1 like MYB transcription factor and TANNIN1 showed strong association with pericarp color validating previous observations. Overall, the genetic architecture of natural variation representing the complex Ethiopian sorghum germplasm was established. The study contributes to the characterization of genes and alleles controlling agronomic traits, and will serve as a source of markers for molecular breeding.